Intercalation chemistry of the novel layered double hydroxides [MAl4(OH)(12)](NO3)(2)center dot gamma H2O (M = Zn, Cu, Ni and Co). 2: Selective intercalation chemistry - Williams, G; Dunbar, T; Beer, A; Fogg, A; O'Hare, D (2006)
The successful intercalation of a variety of organic dicarboxylates and sulfonates into the novel LDHs [MAl4(OH)12](NO 3)2·yH2O (M = Zn, Cu, Ni and Co) has recently been reported [G. R. Williams, T. G. Dunbar, A. J. Beer, A. M. Fogg and D. O'Hare, J. Mater. Chem., DOI: 10.1039/b514874j, ref. 1, the preceeding paper in this issue]. A number of the guests intercalated are isomeric, and the separation of mixtures of these isomers could be useful industrially. Benzenedicarboxylates and napthalenesulfonates were chosen to be the focus of these studies owing to their industrial importance. Preferential intercalation is seen for 1,4-benzenedicarboxylate over 1,2-benzenedicarboxylate, and for 2-naphthelenesulfonate over 1-naphthalanesulfonate. Optimum choice of the reaction conditions can allow almost 100% selectivity for one isomer over another in each case. The intercalation of 1,5-naphthalenedisulfonte over 2,6-naphthalenedisulfonate is found to be less selective (between 45% and 90% of the guest intercalated is 1,5-NDS dependent on the intercalation conditions). The isomer intercalated preferentially can be controlled by the reaction conditions, and by appropriate choice of conditions an almost complete separation of a mixture of these isomers is possible.